Experimental encephalitis caused by Taenia crassiceps cysticerci in mice - Hidelberto Matos-Silva; Bruno Pereira Reciputti; Élbio Cândido de Paula; André Luiz Oliveira; Vânia Beatriz Lopes Moura; Marina Clare Vinaud; Milton Adriano Pelli Oliveira; Ruy de Souza Lino-Júnior (Arquivos de Neuro-Psiquiatria)
OBJECTIVES: To present the experimental model of neurocysticercosis (NCC) caused by Taenia crassiceps cysticerci, to describe the inflammatory process, susceptibility, or resistance of BALB/c and C57BL/6 mice to this infection, and to describe the host-parasite relationship. METHODS: The animals were intracranially inoculated with initial stage T. crassiceps cysticerci. They were euthanized at 7, 30, 60, and 90 days after the inoculation. Their encephala were removed for the histopathologic analysis, classification of the parasites, and inflammatory lesions. RESULTS: Experimental NCC was observed on both mice lineages. BALB/c mice presented inflammatory lesions with greater intensity, inducing necrosis on late stage parasites, and with an acute inflammation pattern, while C57BL/6 mice showed greater capability on provoking early necrosis in the cysticerci, which showed a chronic inflammation pattern. CONCLUSIONS: This experimental model induced NCC on mice with characteristic inflammation and lesions. C57BL/6 mice were able to induce precocious necrosis of the parasites presenting inflammatory lesions with lower intensity.